Effects of Treatment with Various Remineralizing Agents on the Microhardness of Demineralized Enamel Surface - Kiana Salehzadeh Esfahani; Romina Mazaheri; Leila Pishevar (Tabriz University of Medical Sciences, 2015)
Background and aims. Remineralization of incipient caries is one of the goals in dental health care. The present study aimed at comparing the effects of casein phosphopeptide-amorphous calcium phosphate complex (CPP-ACP), Remin Pro®, and 5% sodium fluoride varnish on remineralization of enamel lesions. Materials and methods. In this in vitro study, 60 enamel samples were randomly allocated to six groups of 10. After four days of immersion in demineralizing solution, microhardness of all samples was measured. Afterward, groups 1-3 under-went one-time treatment with fluoride varnish, CPP-ACP, and Remin Pro®, respectively. Microhardness of groups 4-6 was measured not only after one-month treatment with the above-mentioned materials (for eight hours a day), but also after re-exposing to the demineralizing solution. The results were analyzed by one-way analysis of variance (ANOVA), repeated measures ANOVA, and Fisher's least significant difference (LSD) test. Results. None of the regimens could increase microhardness in groups 1-3. However, one-month treatment regimens in groups 4-6 caused a significant increase in microhardness. The greatest microhardness was detected in the group treated with CPP-ACP (P = 0.001). In addition, although microhardness reduced following re-demineralization in all three groups, the mean reduction was minimum in the CPP-ACP-treated group (P < 0.001). Conclusion. While long-term repeated application of all compounds improved microhardness, the remineralization potential of CPP-ACP was significantly higher than that of Remin Pro® and sodium fluoride varnish.